Al Qur’an dalam Praktik Sosial: Hafidzah Sebagai Agen Transformasi - Ismatulloh, AM; Masngudi, Masngudi; Aniroh, Aniroh; Jannah, Zarahtul (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2024)
This research is a study of the living Qur'an, discussing the tradition of reading the Qur'an through semaan activities carried out in Majenang District, Cilacap Regency. In this case, the hafidzah in Majenang District routinely carry out the semaan tradition continuously and periodically from one assembly to another. In this living Qur'an research, the discussion is more focused on how the semaan procession is carried out by hafidzah and what the motives and meaning of the semaan tradition are for the actors/performers of the action. In this case, the actors/perpetrators of this action are the hafidzah students in general, the listeners and the general public. This research uses a qualitative descriptive method with a sociological approach. The data collection techniques that researchers used in this research were participant and non-participant observation, interviews and documentation. Meanwhile, the data analysis used is descriptive-explanatory analysis, apart from making it easier for researchers to explain the content of the discussion, it is also so that they can find out the reasons for the tradition of memorizing the Koran by hafidzah. So that the background, procession, motifs and meaning of the Semaan tradition can be known.